Desain Kemasan Online: Solusi Kreatif dan Terjangkau untuk UMKM melalui Brand PackDe - Ningrat, Rangga Wasita; Rabika, Jonathan Cristiano; Muzaqi, Anggito Rangkuti Bagas; Kuntari, Wien (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Product packaging is an important element in creating the identity and attractiveness of a product, especially for small and medium enterprises (SMEs). This research aims to develop an online-based packaging design service through the PackDe platform that offers easy access, transparent pricing, and a variety of customizable design options. The methods used include literature study, competitor observation, and social media analysis to understand market needs and current design trends. The results show that PackDe is able to provide functional and aesthetic packaging design solutions, supporting SME product branding effectively. Nevertheless, challenges such as limited human resources and marketing need to be overcome to reach a wider market. The implications of this research show that digital-based packaging design innovation can improve the competitiveness of SME products in national and global markets. PackDe is expected to be a strategic partner for SMEs in creating packaging that is not only visually appealing but also has added value to the packaged product.